Preparation of a Polypyrrole/Graphene Oxide Composite Electrode by Electrochemical Codeposition for Capacitor Deionization - Xue, Juanqin (ACS Omega, 2020)
[Image: see text] In this paper, a polypyrrole/graphene oxide (PPy/GO) composite electrode, applied to the capacitive deionization process for removing heavy metal ions, was prepared by one-step electrochemical codeposition. The PPy/GO composite electrode has a dense sheet structure, and PPy is spherical and uniformly distributed on the surface of GO sheets. The experimental results show that the PPy/GO composite electrode has a higher capacitance (186.67 F/g) and a lower charge transfer resistance (1.626 Ω·cm(2)) than the PPy electrode. The adsorption capacity of the PPy/GO composite electrode is 41.51 mg/g, which is about 2.67 times (15.52 mg/g) that of the PPy electrode. After five adsorption/desorption treatments, the adsorption capacity was maintained at about 98.0%, and the regeneration rate was 94.7%. Therefore, the electrode has good cycle stability and regenerability. In addition, the adsorption capacity of different metal ions follows the order Ag(+) < Cd(2+) < Cu(2+) < Pb(2+) < Fe(3+), indicating that the PPy/GO composite electrode has stronger adsorption capacity for the added state, and the adsorption capacity for ions with the same valence state decreases with the increase in ion hydration radius. The PPy/GO composite electrode has a good prospect for the removal of heavy metal ions in industrial wastewater.